Ordered Macro/Microporous Ionic Organic Framework for Efficient Separation of Toxic Pollutants from Water. Issue 1 (7th December 2022) - Fajal, Sahel; Hassan, Atikur; Mandal, Writakshi; Shirolkar, Mandar M.; Let, Sumanta; Das, Neeladri; Ghosh, Sujit K.
Abstract: In case of pollutant segregation, fast mass diffusion is a fundamental criterion in order to achieve improved performance. The rapid mass transport through porous materials can be achieved by availing large open pores followed by easy and complete accessibility of functional sites. Inducing macroporosity into such materials could serve as ideal solution providing access to large macropores that offer unhindered transport of analyte and full exposure to interactive sites. Moreover, the challenge to configure the ionic‐functionality with macroporosity could emerge as an unparalleled avenue toward pollutants separation. Herein, we strategized a synthetic protocol for construction of a positively charged hierarchically‐porous ordered interconnected macro‐structure of organic framework where the size and number of macropores can easily be tuned. The ordered macropores with strong electrostatic interaction synergistically exhibited ultrafast removal efficiency towards various toxic pollutants. Abstract : A charged ordered macro‐micro hierarchical porous organic framework with grafted viologen units is synthesized by a solid‐state acid‐vapor assisted synthetic strategy. The material demonstrates faster diffusion of analytes and ultrafast adsorption potency toward a wider range of organic‐inorganic toxic pollutants from water.